2018
DOI: 10.1108/md-03-2017-0200
|View full text |Cite
|
Sign up to set email alerts
|

Organizational forgetting, absorptive capacity, and innovation performance

Abstract: Purpose The purpose of this paper is to examine how the organizational forgetting affect innovation performance under the consideration of the environmental turbulence as a moderating factor of the analysis framework. Design/methodology/approach This study constructs and verifies a moderated mediating model of organizational forgetting to innovation performance, using the exploratory factor analysis and the hierarchical regression analysis based on a survey sample of 320 Chinese companies. Findings The org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 73 publications
4
42
0
2
Order By: Relevance
“…First, environmental uncertainty. Previous studies have shown that the environmental uncertainty can have a significant impact on business model innovation (Camisón and Villar-López, 2014; Huang et al, 2017). For most of the time, organizations continue to innovate business models (Desarbo et al, 2005) to better fit the changes of market demand in external environments.…”
Section: Methodsmentioning
confidence: 99%
“…First, environmental uncertainty. Previous studies have shown that the environmental uncertainty can have a significant impact on business model innovation (Camisón and Villar-López, 2014; Huang et al, 2017). For most of the time, organizations continue to innovate business models (Desarbo et al, 2005) to better fit the changes of market demand in external environments.…”
Section: Methodsmentioning
confidence: 99%
“…From the theoretical examination of the above literature, this investigation proposed the model of a moderated mediation to further explain in detail that the innovation performance is supported by NHRM practices in the Pakistani semi-government organization context. This model has been developed in the light of earlier HRM studies [94] where the role of innovation climate is proposed as a moderator that adjust the first path of organizational innovation, the structural model presents that the mediating impact of organizational innovation between the NHRM practices and innovation performance is regulated by an innovative climate. The model of study is shown as in Figure 1.…”
Section: Innovative Climate As a Moderatormentioning
confidence: 99%
“…However, to support the result of condition 4, this study followed the guidelines of earlier studies. Huang, et al [94] accepted condition 4 with a low coefficient of 0.02 where innovation performance was regressed on organizational forgetting and absorptive capacity.…”
Section: Oi6mentioning
confidence: 99%
“…Organizational forgetting is the process of disposing of old practices and setting new specifications [13]. Organizational forgetting can also be defined as leaving outdated routines, norms, beliefs, procedures, policies, values and methods while acquiring and assimilating new ones to adapt to changing environments [14]. Then it can be concluded that organizational forgetting is an individual view of a positive consequence that occurs with changes in the company that occur due to loss of knowledge with indicators : intentional loss of knowledge, unintentional loss of knowledge, changes.…”
Section: Organization Forgettingmentioning
confidence: 99%